2021
DOI: 10.1186/s12931-021-01625-y
|View full text |Cite
|
Sign up to set email alerts
|

Post-discharge critical COVID-19 lung function related to severity of radiologic lung involvement at admission

Abstract: Lung function impairment persists in 55% of critical COVID-19 patients three months after ICU discharge. Patient lung function, exercise capacity, radiologic, and quality of life data suggest impairment is related to radiologic lung involvement at admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 22 publications
8
65
2
2
Order By: Relevance
“…Abnormal lung functions and structural changes were reported up to 6 months after hospitalization in mild-to-critical COVID-19 patients ( 25 , 27 , 28 , 32 , 34 , 36 , 39 , 41 ), also with diffuse alveolar damage, desquamation of alveolar epithelial type II cells, fibrine exudation, hyaline membranes, scattered interstitial inflammation, monocytes, and macrophages ( 23 , 24 , 34 ). Several authors reported that these persistent lung symptoms and dysfunctions correlated with prior COVID-19 severity ( 19 , 20 , 24 , 25 , 27 , 36 , 38 , 41 ). In this context, Han et al in a prospective study evaluating 114 severe COVID-19 patients showed lung fibrotic-like changes in 35% patients up to 6 months after infection ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal lung functions and structural changes were reported up to 6 months after hospitalization in mild-to-critical COVID-19 patients ( 25 , 27 , 28 , 32 , 34 , 36 , 39 , 41 ), also with diffuse alveolar damage, desquamation of alveolar epithelial type II cells, fibrine exudation, hyaline membranes, scattered interstitial inflammation, monocytes, and macrophages ( 23 , 24 , 34 ). Several authors reported that these persistent lung symptoms and dysfunctions correlated with prior COVID-19 severity ( 19 , 20 , 24 , 25 , 27 , 36 , 38 , 41 ). In this context, Han et al in a prospective study evaluating 114 severe COVID-19 patients showed lung fibrotic-like changes in 35% patients up to 6 months after infection ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, because is a single case, this research does not provide conclusive evidence. A small cohort of critically ill COVID-19 patients also showed alteration in the diffusing capacity of the lung for carbon monoxide (D LCO ) for up to 3 months ( 20 , 27 , 38 , 40 ). Persistent D LCO impairment was also detected in non-critical COVID-19 patients that also presented shortness of breath and dyspnea up to 4 months after infection ( 18 , 22 , 33 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…A high percentage of adults who recovered from SARS-CoV-2 infection presents with pulmonary dysfunctions even months after the infection ( 15 ). To the best of our knowledge, this is the first study investigating the medium-term effects on pulmonary function of SARS-CoV-2 infection within a pediatric population with typical SARS-CoV-2 respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…About 20-30% of patients who have suffered mild disease may have persisting diminished lung function and exercise capacity, whereas in 55% of patients with critical disease may continue to have the lung function impairment three months following hospital discharge. Further, there has been shown a de inite correlation between initial chest CT scan involvement and impaired PFT [33].…”
Section: Ct Imaging For the Long-term Follow Upmentioning
confidence: 97%